Digitalization as a factor of increasing the motivation of university students in China to physical education on the example of tennis - Kuang Yixin,; Sun Kaiye, (Theory and Practice of Physical Culture, 2025)
In Chinese universities, although education focuses on the impartation of disciplinary knowledge, it also serves as an important pathway to enhance students' physical health, cultivate sports preferences, and improve overall comprehensive qualities. The design of educational tools aims to effectively boost students' learning motivation, particularly by incorporating game elements to enhance their engagement. It hopes to provide new directions for reflection and reference cases for the reform of physical education, offering valuable insights for promoting the high-quality development of digital sports. Objective of the study is to investigate ways of implementing and evaluating the effectiveness of university physical education within the framework of digital sports, both from the point of view of building a theoretical basis and from the point of view of practical research. Methods and structure of the study. A total of 64 students aged 18–20 were divided into experimental and control groups, each subjected to different teaching methods for comparison. Results and conclusions. Pre-test results showed that all 12 items had p-values greater than 0.05 (p>0.05), indicating no significant differences between the experimental (EG) and control groups (CON) prior to the intervention. Post-test results revealed that all p-values were below 0.05 or 0.01, demonstrating that the experimental group scored significantly higher than the control group across all dimensions of intrinsic motivation. The experimental teaching method (incorporating VR, intelligent systems, and online interaction) significantly enhanced students' intrinsic motivation, whereas the traditional approach failed to maintain or improve motivation levels, even showing slight declines.